Methodological approaches to the assessment of orphan medicinal products when making decisions about their inclusion in the program of medicinal maintenance: international experience and possible ways of its adaptation to the conditions of the health care system of the russian federation - N. G. Goloenko; R. I. Yagudina; V. G. Serpik; A. Yu. Kulikov (Безопасность и риск фармакотерапии, 2018)
The article presents a first attempt of implementation of the methodology multicriteriale analysis of decision making in the organization of the system of drug provision in the Russia. In this paper, the reasons to update the activity aimed to implement the described methodology, as well as a dedicated area of drug supply, which multicriterial analysis of decision-making is most in demand - namely, for the organization of drug provision of patients with orphan diseases.